Effect of the human therapeutic drug diltiazem on the haematological parameters, histology and selected enzymatic activities of rainbow trout Oncorhynchus mykiss. (August 2016) - Steinbach, Christoph; Burkina, Viktoriia; Schmidt-Posthaus, Heike; Stara, Alzbeta; Kolarova, Jitka; Velisek, Josef; Randak, Tomas; Kroupova, Hana Kocour
Abstract: Diltiazem is a pharmaceutical belonging to a group of calcium channel blockers (CCB) that is widely used in the treatment of angina pectoris and hypertension. The objective of the present study was to assess the effect of diltiazem on rainbow trout ( Oncorhynchus mykiss ). Juvenile trout were exposed for 21 and 42 days to three nominal concentrations of diltiazem: 0.03 μg L −1 (environmentally relevant concentration), 3 μg L −1, and 30 μg L −1 (sub-lethal concentrations). The number of mature neutrophilic granulocytes was significantly increased by 450 and 400% in fish exposed to 3 μg L −1 and 30 μg L −1 diltiazem compared to the control, respectively. Antioxidant enzyme activity was affected in liver and gills of fish exposed to all tested concentrations of diltiazem but the changes were mostly transient and not concentration dependent. Creatine kinase activity was markedly increased (ranging from 520 to 845%) at all tested diltiazem concentrations at the end of the exposure indicating muscle and/or kidney damage. The highest concentration was associated with histological changes in heart, liver, and kidney. These alterations can be attributed to the effects of diltiazem on the cardiovascular system, similar to those observed in the human body, as well as to its metabolism. At the environmentally relevant concentration, diltiazem was found to induce some alterations in the blood, gills, and liver of fish, indicating its potential for adverse effects on non-target organisms in the aquatic environment. Highlights: Diltiazem at concentrations of 3 and 30 μg L −1 affected the haematological and blood biochemical profile of rainbow trout. Creatine kinase activity was markedly increased at all tested diltiazem concentrations at the end of the exposure. Diltiazem exposed fish (30 μg L −1 ) showed scattered to mild histopathological changes in liver, kidney and heart. Antioxidant enzyme activity in liver and gills of trout at an environmentally relevant concentration was slightly affected.